Impact of Window-to-Wall Ratio on Lighting Load in Municipality Building-A Case Study of Bharatpur Metropolitan Administration Bloc - Shrestha, Rohit; Uprety, Sanjaya (Kathford Journal of Engineering and Management, 2023)
Visual comfort is a critical aspect of indoor environments, contributing to occupant satisfaction, well-being, and overall productivity. In the face of rapid urbanization, particularly in regions like the Chitwan District, understanding and enhancing visual comfort in built environments take on heightened significance. The primary focus of this study is to explore how varying Window-Wall Ratios (WWR) affect the energy performance of buildings. The research begins with an in-depth review of existing literature on building energy efficiency, focusing on the significance of WWR in determining natural lighting penetration. Field measurements are collected to establish a baseline understanding of the building’s lighting performance. Utilizing advanced simulation tools, the study explores various WWR scenarios to simulate the potential impact on lighting load. The analysis considers both energy efficiency and occupant comfort, aiming to identify an optimal WWR that balances natural lighting benefits with energy conservation goals. The study finds that a 30% WWR represents the ideal balance for effective electricity consumption for lighting. Monthly analysis underscores its significance by revealing diminishing returns beyond this point. Consequently, recommended optimal WWR values stand at 25% for the ground floor and 30% for both the first and top floors. The findings hold significant importance for designers and policymakers in making informed design and policy decisions.